Pharmacist-Managed Helicobacter pylori Treatment Service Within a Gastroenterology Clinic: Workflow and Real-World Experiences. Issue 2 (February 2022) - Bhat, Shubha; Nunes, David
Background: Treatment eradication rates of Helicobacter pylori, a gastrointestinal infection, are 70% to 90% in clinical studies but lower in real-world settings. Potential barriers include multidrug regimen complexity or prescribing/administration errors. A pharmacist-managed H pylori treatment service was implemented to address these barriers and optimize treatment outcomes. The clinical pharmacist provided 2 services: (1) treatment education and monitoring for treatment-naïve patients and (2) treatment initiation, education, and monitoring for treatment-experienced patients. Objective: We aimed to evaluate the impact of a pharmacist-managed H pylori treatment service within a gastroenterology clinic. Methods: We conducted a retrospective observational cohort study of all patients referred to and seen in the pharmacist-managed H pylori treatment service from July 10, 2019, to December 31, 2020. Patient demographics, prior treatment history, course(s) of treatment prescribed, frequency of follow-ups, and outcomes posttreatment were collected. Results: The clinical pharmacist managed 60 referrals for 55 unique patients over a mean of 5 ± 2 visits. Five patients failed H pylori treatment and were re-referred. Identified barriers included prescribing/dispensing and administration errors. Posttreatment, 38 referrals tested for H pylori eradication, of which 100% of treatment-naïve patients and 69% of treatment-experienced patients were cured, and 13 (22%) referrals were lost to follow-up. Conclusion and Relevance: This study described and assessed the impact of a pharmacist-managed H pylori treatment service in a gastroenterology clinic, in which various barriers were effectively addressed to optimize treatment outcomes. Future studies should focus on long-term outcome, impact on health care costs, and patient satisfaction with this service.